2007
DOI: 10.1185/030079908x260835
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of insulin detemir basal-bolus therapy in type 1 diabetes patients: 14-week data from the European cohort of the PREDICTIVE study

Abstract: In this open-label, prospective, observational study, insulin detemir basal-bolus therapy improved glycaemic control and reduced hypoglycaemia with weight neutrality in type 1 patients in actual clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
5
23
0
Order By: Relevance
“…In the German cohort of PREDICTIVE study, major hypoglycemia was significantly reduced by 55% and 51% respectively in prior NPH and glargine insulin users who switched to IDet. 19 The safety related findings of the present study are important as they have been obtained during routine clinical practice and are more realistic than those observed within the controlled environment of clinical trials. On the other hand there might also be under reporting of hypoglycemia in this study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the German cohort of PREDICTIVE study, major hypoglycemia was significantly reduced by 55% and 51% respectively in prior NPH and glargine insulin users who switched to IDet. 19 The safety related findings of the present study are important as they have been obtained during routine clinical practice and are more realistic than those observed within the controlled environment of clinical trials. On the other hand there might also be under reporting of hypoglycemia in this study.…”
Section: Discussionmentioning
confidence: 76%
“…17,18 Interestingly, switching from glargine insulin based regimen to IDet had also led to further 0.6% reduction in HbA1c. 19 Patients with long duration of diabetes often require intensive insulin therapy for optimal glycemic control. However, intensive insulin therapy whilst improving glycemic control is associated with increased risk of hypoglycemia leading to significant morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the PREDICTIVE study (2008) were the source of data on efficacy and safety of various basal-bolus insulin therapy regimens [8,9]. The following analyses were performed in the pharmacoeconomic study: cost-effectiveness, cost-benefit and budget impact [10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…PREDICTIVE was a multicenter, multi-national, observational study initially intended to assess the safety and efficacy of insulin detemir in patients with diabetes [8,9]. The European cohort included 20,531 patients with diabetes (7,420 with T1DM) from 11 countries.…”
mentioning
confidence: 99%
“…A recent study in patients with type 1 diabetes mellitus with severe hypoglycaemia on NPH who were changed to glargine or detemir still experienced severe hypoglycaemia and few patients reached internationally accepted glycaemic treatment goals [35]. In fact a Cochrane review article showed no glycaemic benefit of long-acting insulin analogues compared with intermediate-acting insulin [36].…”
Section: Hypoglycaemiamentioning
confidence: 99%